1996
DOI: 10.1007/bf02207273
|View full text |Cite
|
Sign up to set email alerts
|

A volume-activated anion conductance in insulin-secreting cells

Abstract: The whole-cell patch-clamp recording technique was used to measure volume-activated currents in K+-free solutions in RINm5F and HIT-T15 insulinoma cells and in dispersed rat islet cells. Cell swelling, induced by intracellular hypertonicity or extracellular hypotonicity, caused activation of an outwardly rectifying conductance which could be subsequently inactivated by hypertonic extracellular solutions. The conductance required adenosine 5'-triphosphate (ATP) in the pipette solution but was Ca2+ independent. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
98
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 26 publications
12
98
2
Order By: Relevance
“…This result may seem inconsistent with a previous report from this laboratory indicating that electrical activity in response to a high concentration of tolbutamide was resistant to inhibition by DIDS [18]. However, it should be noted that DIDS is a relatively weak inhibitor of the VRAC, particularly the inward current component [7]. This could explain why DIDS failed to inhibit the effects of a high concentration of tolbutamide but was effective in inhibiting electrical activity evoked by a lower concentration of the sulphonylurea in the present study.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…This result may seem inconsistent with a previous report from this laboratory indicating that electrical activity in response to a high concentration of tolbutamide was resistant to inhibition by DIDS [18]. However, it should be noted that DIDS is a relatively weak inhibitor of the VRAC, particularly the inward current component [7]. This could explain why DIDS failed to inhibit the effects of a high concentration of tolbutamide but was effective in inhibiting electrical activity evoked by a lower concentration of the sulphonylurea in the present study.…”
Section: Discussioncontrasting
confidence: 98%
“…Since direct recordings of K ATP channel activity indicate that these channels are closed at glucose concentrations of 5 mmol/l and above [5], it is likely that sulphonylureas can exert additional ionic effects on the beta cell. The aim of the present study was to test the hypothesis that sulphonylureas influence the glucose-and volume-regulated anion channel (VRAC) current previously described in beta cells [6,7].…”
Section: Introductionmentioning
confidence: 98%
“…The discovery of a novel anion-selective channel in pancreatic islet ␤-cells by Kinard and Satin (5) and Best et al (6) suggests that some of the previously observed effects of anions on islet function may be mediated by an anion-permeable ion channel. This anion-permeable pancreatic islet ␤-cell Cl Ϫ channel (I Cl,islet ) is an outwardly rectifying Cl Ϫ channel that is activated by cell swelling (induced by the application of hypotonic solution) or by a rise in intracellular cAMP (5).…”
mentioning
confidence: 99%
“…I Cl,islet is inhibited by the well-known Cl Ϫ channel blocker 4,4Ј-diisothiocyanatostilbene-2,2Ј-disulfonic acid (DIDS) or by 100 mol/l glyburide (5). The channel may also be under metabolic control, either by virtue of its sensitivity to intracellular ATP (5,6) or because of ␤-cell swelling associated with increased glucose metabolism (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation